Pengembangan Model Pembelajaran Interaksi dan Komunikasi Bagi Anak Autis - Abdul Rahim; Endang Hangesti Ningsih; Taryatman (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2020)
The research aims to develop interaction and communication learning models for autistic children. This research is expected to be a reference for therapists, teachers and parents in providing intervention services for children with autism in developing interaction and communication skills. This study uses an experimental method, with a single subject approach or single subject research (SSR). SSR refers to the research strategy developed to document changes in the subject's individual behavior. The model used is model A - B - A design. The results showed that the development of interaction and communication learning models for children with autism was carried out with 3 (three) stages, namely: 1) planning with the aim of obtaining data on reinforcement sampling and symbol assessment as reinforcement given to children with autism when the intervention was carried out, 2) stages implementation is carried out at least 10 sessions for each aspect to be intervened and every intervention is carried out recording (field recording), 3) the evaluation phase that needs to be considered is reinforcement and the media used are interesting or even less attractive to the subject.